Armenia Country Gender Assessment 2016 - World Bank (World Bank, Washington, DC, 2017)
This Country Gender Assessment (CGA) reviews the state of equality between women and men in Armenia in access to opportunities, that is, equality in rights, resources, and voice (World Bank 2007). Equality in rights refers to equality under the law, whether customary or statutory. Equality in resources refers to equality in access to human capital investments, productive resources, and markets. Equality in voice refers to the capacity to make decisions about one’s own life, to act on these decisions, and to influence and contribute to political discourse and the development process. Noting the government’s commitment to gender equality in the legal framework and in policies, this report mainly focuses on the extent of equality in resources and voice. Specifically, the report reviews the extent of equality in the areas of demography, human capital, economic opportunities, and voice and agency. It also points to some common patterns.